2006
DOI: 10.2220/biomedres.27.139
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal regeneration following transplantation of proliferating tissue derived from periodontal ligament into class III furcation defects in dogs

Abstract: The aim of this study was to evaluate the healing of class III furcation defects following

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…These findings are in accordance with previous studies, which demonstrated the potential of in situ tissue engineering using PDL cells for the periodontal regeneration (Nakahara et al 2004, Akizuki et al 2005, Murano et al 2006, Gault et al 2010). Nakahara et al (2004), evaluating the effect of PDL cells seeded on periodontal fenestration defects, demonstrated that these cells induced cementum regeneration on the root surface.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are in accordance with previous studies, which demonstrated the potential of in situ tissue engineering using PDL cells for the periodontal regeneration (Nakahara et al 2004, Akizuki et al 2005, Murano et al 2006, Gault et al 2010). Nakahara et al (2004), evaluating the effect of PDL cells seeded on periodontal fenestration defects, demonstrated that these cells induced cementum regeneration on the root surface.…”
Section: Discussionsupporting
confidence: 93%
“…Fenestration and dehiscence defects, used in previous studies, have thin buccal alveolar plate and promote minimal space between the flap and the root surface contributing for the lack of effect in the bone regeneration. On the other hand, similar positive bone response was reported by Murano et al (2006) that applied PDL cells in class III furcation in dogs and observed an accelerated bone formation (84.8%) when compared with the control group (12.2%).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“… reported a study involving 15 mixed‐breed dogs, in which the use of tissue derived from periodontal ligament to regenerate Class III furcation defects was evaluated, and identified that implantation of tissue containing periodontal ligament‐derived cells significantly increased the extent of periodontal tissue and cementum regeneration covering the circumference of the defect in dogs that received periodontal ligament tissue compared with controls. Additionally, implantation of periodontal ligament tissue increased the amount of new bone formation, with 84.8 ± 3.9% of the defect height being filled with new bone in the periodontal ligament tissue group compared with 12.2 ± 1.3% ( p < 0.01) in control animals . The periodontal ligament‐derived cells used in these experiments were obtained using a similar protocol to that used by Dogan et al .…”
Section: Resultsmentioning
confidence: 99%
“…Tissue engineering principles may provide new approaches to overcome the obstacles encountered during the attempts to regenerate the periodontal tissues. Tissue engineering applications to engineer the periodontal tissues using PDL cells, cementoblasts, bone marrow stromal cells, and periosteal cells have provided promising result in animal models 5–9…”
Section: Introductionmentioning
confidence: 99%